A Review of Malaysian Medicinal Plants with Potential Anti-Inflammatory Activity - Fazleen Izzany Abu Bakar; Mohd Fadzelly Abu Bakar; Norazlin Abdullah; Susi Endrini; Asmah Rahmat (Hindawi Limited, 2018)
This article aims to provide detailed information on Malaysian plants used for treating inflammation. An extensive search on electronic databases including PubMed, Google Scholar, Scopus, and ScienceDirect and conference papers was done to find relevant articles on anti-inflammatory activity of Malaysian medicinal plants. The keyword search terms used were "inflammation," "Malaysia," "medicinal plants," "mechanisms," "in vitro," and "in vivo." As a result, 96 articles on anti-inflammatory activity of Malaysian medicinal plants were found and further reviewed. Forty-six (46) plants (in vitro) and 30 plants (in vivo) have been identified to possess anti-inflammatory activity where two plants, Melicope ptelefolia (Tenggek burung) and Portulaca oleracea (Gelang pasir), were reported to have the strongest anti-inflammatory activity of more than 90% at a concentration of 250 µg/ml. It was showed that the activity was mainly due to the occurrence of diverse naturally occurring phytochemicals from diverse groups such as flavonoids, coumarins, alkaloids, steroids, benzophenone, triterpenoids, curcuminoids, and cinnamic acid. Hence, this current review is a detailed discussion on the potential of Malaysian medicinal plants as an anti-inflammatory agent from the previous studies. However, further investigation on the possible underlying mechanisms and isolation of active compounds still remains to be investigated.